Analysis Of Understanding Hadith Towards The Legitimation Of The Death Criminal For Apostasy - Suci Ramadhan (Syariah: Jurnal Hukum dan Pemikiran, 2022)
Abstract: The discourse on the implementation of punishment for apostates still become critical and problematic debates among Islamic scholars. This debate is motivated by the existence of hadith texts which explicitly narrate that the criminal sanction for apostates is the death penalty. This study aims to analyze the death penalty for apostates based on hadith texts. This research is normative research with a text approach and hadith context. The data source uses hadith texts related to the death penalty for apostates “man baddala dīnahu fa uqtulūh” and uses descriptive qualitative analysis. The study confirms that the implementation of the hadiths regarding the death penalty for apostates is closely related to the context of space and time when these hadiths were revealed. Based on the sociohistorical perspective, the death penalty for apostates is not a criminal sanction applied to their apostasy. However, these sanctions are carried out for criminal acts such as intentional murder and hate speech or lies in the name of Islam so as to disrupt the stability of the security of society and the state. Thus, the hadith texts regarding the death penalty cannot be used as legal legitimacy to punish the apostasy act. Abstrak: Diskursus penerapan pidana bagi pelaku murtad masih meniscayakan perdebatan kritis dan problematis di kalangan ulama klasik maupun kontemporer. Perdebatan ini dilatarbelakangi adanya teks-teks hadits yang menarasikan secara eksplisit bahwa sanksi pidana bagi pelaku murtad adalah hukuman mati. Penelitian ini bertujuan untuk menganalisis tindak pidana mati bagi pelaku murtad berdasarkan teks-teks hadits. Penelitian ini merupakan penelitian normatif dengan pendekatan teks dan konteks hadits. Sumber data menggunakan teks-teks hadits hukuman mati bagi murtad “man baddala dīnahu fa uqtulūh” dan kemudian analisis data menggunakan analisis kualitatif deskriptif. Hasil penelitian ini menegaskan bahwa penerapan hadits-hadits tentang hukuman mati bagi pelaku murtad sangat erat kaitannya dengan konteks ruang dan waktu di masa turunnya hadits-hadits tersebut. Menurut perspektif sosiohistoris, sanksi pidana mati bagi pelaku murtad dalam teks-teks hadits bukanlah sebagai sanksi yang diterapkan atas kemurdatannya. Namun, sanksi tersebut diterapkan atas tindakan kriminalnya yakni pembunuhan yang disengaja dan ujaran kebencian atau kebohongan atas nama Islam sehingga mengganggu stabilitas keamanan masyarakat dan negara. Dengan demikian, teks-teks hadits yang berbicara tentang hukuman pidana mati tidak dapat dijadikan legitimasi hukum dan pertimbangan untuk memberikan sanksi pidana mati perbuatan murtad.